The Impact of Teacher Empathy on Cognitive and Emotional Development: Insights from Primary School Students in the Arab Sector in Israel - Awawda, Jumana Sobhi; Bashir, Yasir Riad (Journal of Posthumanism, 2025)
This study examines the level of empathy among elementary school teachers in the Arab sector in Israel and its impact on students’ emotional and cognitive development. It also explores whether statistically significant differences exist in teachers’ empathy levels and students’ emotional and cognitive development based on demographic variables (gender and grade). A descriptive correlational research design was employed, using a questionnaire to assess teacher empathy and its influence on students. The sample included 372 male and female students randomly selected from various elementary schools in the Arab sector in Israel. Data were analyzed using SPSS through descriptive statistics, t-tests, and analysis of variance (ANOVA). The findings indicate that teachers generally demonstrate a high level of empathy, with students expressing appreciation for teachers’ support and respectful interactions regardless of academic performance. A positive relationship was found between teacher-provided emotional and cognitive support and students’ ability to engage, express emotions, and achieve academic success. The study recommends strengthening the emotional dimensions of teacher-student relationships, particularly in supporting students experiencing sadness or anxiety, to foster a positive and supportive learning environment conducive to both emotional and cognitive growth. Furthermore, the study proposes several practical recommendations, including the development of training modules for teachers to enhance empathy, and policy-level interventions by school leadership to promote emotional well-being and inclusive educational practices. Interpretive analysis of interviews with teachers and students further reinforced these findings. Teachers viewed empathy not only as a means of emotional support but also as a foundation for building trust and ensuring a safe learning environment. Students reported increased comfort and engagement in classrooms where emotional and academic support were present. Many highlighted that teacher empathy helped reduce anxiety, boost self-confidence, and enhance their sense of security, thereby positively influencing academic performance.